MODERASI BERAGAMA MELALUI PEMBELAJARAN MATEMATIKA DI MADRASAH IBTIDAIYAH - Supriyanto (PREMIERE : Journal of Islamic Elementary Education, 2024)
Religious moderation is a crucial concept in fostering tolerance and respect for diversity in multicultural societies. In Indonesia, Madrasah Ibtidaiyah (Islamic elementary schools) play a significant role in instilling the values of religious moderation as faith-based educational institutions. This article explores how mathematics learning can serve as a tool for teaching religious moderation in Madrasah Ibtidaiyah. The study employs a qualitative approach with a literature review method, conducting thematic analysis of various scholarly journals. The findings indicate that mathematics education not only enhances cognitive skills but also helps shape students' character, promoting inclusivity and tolerance. By integrating religious moderation values—such as justice (al-'adl), balance (tawazun), and tolerance (tasamuh)—into math lessons (e.g., through contextual word problems or group discussions), Madrasah Ibtidaiyah can strengthen students' ethical and social awareness alongside their academic abilities. This research highlights the potential of mathematics as an interdisciplinary medium for nurturing moderate, pluralism-friendly attitudes in young learners.